2016
DOI: 10.1186/s40349-016-0066-7
|View full text |Cite|
|
Sign up to set email alerts
|

Open-source, small-animal magnetic resonance-guided focused ultrasound system

Abstract: BackgroundMR-guided focused ultrasound or high-intensity focused ultrasound (MRgFUS/MRgHIFU) is a non-invasive therapeutic modality with many potential applications in areas such as cancer therapy, drug delivery, and blood-brain barrier opening. However, the large financial costs involved in developing preclinical MRgFUS systems represent a barrier to research groups interested in developing new techniques and applications. We aim to mitigate these challenges by detailing a validated, open-source preclinical M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…Three baseline preheating images were acquired of all slices before triggering the laser(s) for a 30 seconds INI heating image. The acquired images were zero‐padded in‐plane to a 512 × 512 matrix (0.055 × 0.055 × 0.25 mm voxels) and temperature maps were computed from the resulting images using baseline‐subtracted proton resonance frequency‐shift MR thermometry which was adapted to run on the scanner .…”
Section: Methodsmentioning
confidence: 99%
“…Three baseline preheating images were acquired of all slices before triggering the laser(s) for a 30 seconds INI heating image. The acquired images were zero‐padded in‐plane to a 512 × 512 matrix (0.055 × 0.055 × 0.25 mm voxels) and temperature maps were computed from the resulting images using baseline‐subtracted proton resonance frequency‐shift MR thermometry which was adapted to run on the scanner .…”
Section: Methodsmentioning
confidence: 99%
“…For example, voxel temperatures were allowed to exceed the mild range since feedback control was not used. Our group has experience with mild hyperthermia feedback (e.g., Poorman et al [ 31 ]) but the present study was instead designed to observe the onset of cavitation at matched powers, and we showed that it is less likely to occur in multi-focusing at a given input power.…”
Section: Discussionmentioning
confidence: 80%
“…Currently, the only device that can do this 20 uses phased arrays, which steer the beam electronically. To our knowledge, there is another single‐element transducer system for small animals 31 but with a completely different design. The design of the system is simpler yet as effective as phased arrays, and the production cost is affordable, since sonications are performed via a monoelement focused transducer.…”
Section: Discussionmentioning
confidence: 99%